IMPLEMENTATION OF CARBON TAX IN INDONESIA FROM A CARBON TAX DESIGN PERSPECTIVE - Vissia Dewi Haptari; Budiasih Widiastuti (SEAN Institute, 2023)
Carbon emissions encompass all aspects of the economic and social fabric of society, thereby creating negative externalities for the public, necessitating government intervention. Various efforts have been made to curb carbon emissions, including the imposition of a carbon tax. The implementation of a carbon tax in Indonesia is inseparable from the regulations outlined in the Harmonization of Tax Regulation Law, which includes the roadmap for carbon taxation and carbon market development. Policies and plans for the implementation of a carbon tax require comprehensive planning from various determinants, namely factors in implementation, the object of the carbon tax, the sectors subject to it, subjects, rates, collection mechanisms, the timing of carbon tax imposition, reduced emission impacts, and revenue potential determination. The phased implementation strategy of carbon tax policies, building a coalition that supports such policies, precise management of carbon tax revenue, and combining carbon tax policies with other climate-related policies can be a solution for the government to address challenges in the carbon tax policy implementation process.